The regulative role and mechanism of BNST in anxiety disorder - Xie, Mingjun; Xiong, Ying; Wang, Haijun (Frontiers in Psychiatry, 2024)
Anxiety disorders, common yet impactful emotional disturbances, significantly affect physical and mental health globally. Many neuron circuits are associated with anxiety regulation like septo-hippocampal loop, amygdala(AMYG), bed nucleus of the stria terminalis (BNST), ventral hippocampus (vHPC), and brain regions like medial prefrontal cortex (mPFC). However, the concrete mechanism of anxiety disorder in BNST is relatively unknown. Recent research showed BNST plays a critical role in modulating anxiety owing to its anatomical location and special circuit characteristics, which are considered to be a hub in the limbic system regulating anxiety. BNST consists with multiple subregions, which can project separately into different brain regions and exert projecting independently to various brain regions with distinct regulatory effects. Moreover, multiple signal pathways in BNST are reported to play significant roles in regulating anxiety and stress behavior. This review briefly describes anxiety disorders and subdivisions and functions of BNST, focusing on the main neural circuits that serve as fundamental pathways in both the genesis and potential treatment of anxiety disorders and the molecular mechanism of BNST on anxiety. The complexity of structures and mechanisms has facilitated the development of imaging techniques. Innovative multimodal imaging techniques, such as functional magnetic resonance imaging (fMRI) and positron emission tomography (PET), have non-invasively illuminated BNST activities and their functional connections with other brain areas. These methodologies provide a deeper understanding of how BNST responds to anxiety-inducing stimuli, offering invaluable insights into its complex role in anxiety regulation. The continued exploration of BNST in anxiety research promises not only to elucidate fundamental neurobiological mechanisms but also to foster advancements in clinical treatments for anxiety disorders.